2020
DOI: 10.1002/adhm.202000122
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Controlled Cortical Impact Injury in 3D Brain‐Like Tissue Cultures

Abstract: Traumatic brain injury (TBI) survivors suffer long term from mental illness, neurodegeneration, and neuroinflammation. Studies of 3D tissue models have provided new insights into the pathobiology of many brain diseases. Here, a 3D in vitro contusion model is developed consisting of mouse cortical neurons grown on a silk scaffold embedded in collagen and used outcomes from an in vivo model for benchmarking. Molecular, cellular, and network events are characterized in response to controlled cortical impact (CCI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Confocal z stack images at 1, 2, and 3 weeks of culture showed that neurons formed extensive 3D structural networks ( Figures 2 A and 2B, and Video S1 ). Using a custom MATLAB code to quantify the 3D neurite density (( Liaudanskaya et al, 2020 ) and detailed in Transparent Methods ), we observed an increase in neurite density over the course of development ( Figure 2 C). To provide further evidence of structural network formation, quantitative real-time PCR (qRT-PCR) was used to analyze the expression of genes known to change during neural development.…”
Section: Resultsmentioning
confidence: 99%
“…Confocal z stack images at 1, 2, and 3 weeks of culture showed that neurons formed extensive 3D structural networks ( Figures 2 A and 2B, and Video S1 ). Using a custom MATLAB code to quantify the 3D neurite density (( Liaudanskaya et al, 2020 ) and detailed in Transparent Methods ), we observed an increase in neurite density over the course of development ( Figure 2 C). To provide further evidence of structural network formation, quantitative real-time PCR (qRT-PCR) was used to analyze the expression of genes known to change during neural development.…”
Section: Resultsmentioning
confidence: 99%
“…We used three-dimensional human endothelial cell cultures to assess cell autonomous responses to TBI in vitro and draw parallels to the human condition [ 36 ]. We subjected human brain endothelial cells in three-dimensional silk scaffold cultures to trauma using the same CCI device and injury parameters as in vivo [ 32 ]. In human endothelial cells, significant induction of both total (1.4-fold) and phospho-RIPK3 (2.1-fold) was observed at 24 h in injured vs. sham injured cultures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Three-dimensional scaffolds of human brain endothelial cells were placed on a cell culture dish and subjected to CCI using the same apparatus used for in vivo CCI (6 m/s, 1.2 mm depth) or to sham injury (no impact) as previously described [ 32 ]. Cultures were then returned to media and incubated at 37 °C for 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported several in vitro brain models, with both primary rodent neurons and human induced pluripotent stem cells (iPSCs), using porous scaffolds fabricated with silk fibroin and extracellular matrix composites. Such models recapitulated many key features of the brain tissue ( Cairns et al., 2020 ; Cantley et al., 2018 ; Dingle et al., 2020 ; Liaudanskaya et al., 2020 ; Rouleau et al., 2020 ; Tang-Schomer et al., 2014 ).…”
Section: Before You Beginmentioning
confidence: 96%